Production of monoclonal antibodies to group A erythrocytes, HLA and other human cell surface antigens-new tools for genetic analysis. - Barnstable, C; Bodmer, W; Brown, G; Galfre, G; Milstein, C; Williams, A; Ziegler, A (1978)
Antibody-secreting hybrid cells have been derived from a fusion between mouse myeloma cells and spleen cells from a mouse immunized with membrane from human tonsil lymphocyte preparations. Hybrids secreting antibodies to cell surface antigens were detected by assaying culture supernatants for antibody binding to human tonsil cells. Six different antibodies (called W6/1, /28, /32, /34, /45 and /46 were analyzed. These were either against antigens of wide tissue distribution (W6/32, /34, and /46) or mainly on erythrocytes (W6/1 and W6/28). One of the anti-erythrocyte antibodies (W6/1) detected a polymorphic antigen, since blood group A1 and A2 erythrocytes were labeled while B and O were not. Antibodies W6/34, /45 and /46 were all against antigens which were mapped to the short arm of chromosome 11 by segregation analysis of mouse-human hybrids. Immunoprecipitation studies suggest that W6/45 antigen may be a protein of 16,000 dalton, apparent molecular weight, while W6/34 and /46 antigens could not be detected by this technique. Antibody W6/32 is against a determinant common to most, if not all, of the 43,000 dalton molecular weight chains of HLA-A, B and C antigens. This was established by somatic cell genetic techniques and by immunoprecipitation analysis. Tonsil leucocytes bound 370,000 W6/32 antibody molecules per cell at saturation. The hybrid myelomas W6/32 and W6/34 have been cloned, and both secrete an IgG2 antibody. W6/32 cells were grown in mice, and the serum of the tumor-bearing animals contained greater than 10 mg/ml of monoclonal antibody. The experiments established the usefulness of the bybrid myeloma technique in preparing monospecific antibodies against human cell surface antigens. In particular, this study highlights the possibilities not only of obtaining reagents for somatic cell genetics, but also of obtaining mouse antibodies detecting human antigenic polymorphisms.